1997
DOI: 10.1002/(sici)1097-4547(19970315)47:6<561::aid-jnr1>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor modulates GAP-43 but not t?1 expression in injured retinal ganglion cells of adult rats

Abstract: The administration of neurotrophins affects neuronal survival and growth, but less is known about their ability to modify the expression of growth associated genes following injury to CNS neurons. Here we characterize the effect of brain‐derived neurotrophic factor (BDNF) on mRNA levels for Tα1 α‐tubulin, and for GAP‐43, two genes whose expression levels in retinal ganglion cells (RGC) tend to correlate with growth. We first determined that most adult rat RGCs can retrogradely transport BDNF by injecting 125I‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…BDN F has been suggested to be a trophic factor derived from the tectum, and expression of BDN F mRNA in the tectum of several different species supports this hypothesis (Leibrock et al, 1989;Cohen-Cory and Fraser, 1994;). Attempts to demonstrate retrograde transport of NGF in this system failed (Yip and Johnson, 1983;C armignoto et al, 1989), although BDN F is transported from the tectum to the retina in adult rat (Fournier et al, 1997). Our data show that neurons of the retinorecipient layers of the optic tectum express BDNF, and we demonstrate, for the first time, that exogenously applied BDN F is transported from the tectum to the retina in the developing animal.…”
Section: Bdnf As a Target-derived Trophic Factorsupporting
confidence: 44%
“…BDN F has been suggested to be a trophic factor derived from the tectum, and expression of BDN F mRNA in the tectum of several different species supports this hypothesis (Leibrock et al, 1989;Cohen-Cory and Fraser, 1994;). Attempts to demonstrate retrograde transport of NGF in this system failed (Yip and Johnson, 1983;C armignoto et al, 1989), although BDN F is transported from the tectum to the retina in adult rat (Fournier et al, 1997). Our data show that neurons of the retinorecipient layers of the optic tectum express BDNF, and we demonstrate, for the first time, that exogenously applied BDN F is transported from the tectum to the retina in the developing animal.…”
Section: Bdnf As a Target-derived Trophic Factorsupporting
confidence: 44%
“…The intravitreal administration of a single dose of BDNF to axotomized RGCs on the day of injury caused a moderate and shortlasting enhancement in GAP-43 mRNA levels in most RGCs during the first week after axotomy. It was suggested that the changes in GAP-43 expression correlated with the branching of injured neurons [45]. Effects of BDNF on GAP-43 mRNA expression might be mediated by a Nitric Oxide (NO)-dependent mechanism [46].…”
Section: Discussionmentioning
confidence: 99%
“…Developmentally, RGCs express this protein during axon outgrowth and synaptic refinement, then downregulate it as their connections mature (Skene and Willard, 1981b;Meiri et al, 1986;Moya et al, 1988). Normally, GAP-43 is transiently upregulated after axotomy and declines as RGCs undergo atrophic changes (Doster et al, 1991;Fournier et al, 1997;Wodarczyk et al, 1997;Wouters et al, 1998). Levels remain high only if regeneration is sustained (Skene and Willard, 1981a;Benowitz and Lewis, 1983;Doster et al, 1991;Meyer et al, 1994;Schaden et al, 1994;Berry et al, 1996).…”
Section: Discussionmentioning
confidence: 99%